Nanoparticles isolated from blood: a reflection of vesiculability of blood cells during the isolation process - Šuštar V (Dove Medical Press, 2011)
Vid Šuštar1, Apolonija Bedina-Zavec1,2, Roman Štukelj1, Mojca Frank3, Goran Bobojevic1, Rado Janša4, Eva Ogorevc5, Peter Kruljc6, Keriya Mam7, Boštjan Šimunic8, Mateja Mancek-Keber9, Roman Jerala9, Blaž Rozman3, Peter Veranic10, Henry Hägerstrand11, Veronika Kralj-Iglic11Laboratory of Clinical Biophysics, Faculty of Medicine, University of Ljubljana, Ljubljana, Slovenia; 2Laboratory of Biosynthesis and Biotransformation, National Institute of Chemistry, Ljubljana, Slovenia; 3Departments of Rheumatology; 4Gastroenterology, Ljubljana University Medical Centre, Ljubljana, Slovenia; 5Laboratory of Biophysics, Faculty of Electrical Engineering; 6Clinics for Reproduction and Horses, Faculty of Veterinary Medicine, University of Ljubljana, Ljubljana, Slovenia; 7FEI Quanta, Eindhoven, The Netherlands; 8Laboratory of Biotechnology, National Institute of Chemistry, Ljubljana, Slovenia; 9University of Primorska, Science and Research Centre of Koper, Koper, Slovenia; 10Institute of Cell Biology, Faculty of Medicine, University of Ljubljana, Ljubljana, Slovenia; 11Department of Biosciences, Biocity, Åbo Akademi University, Åbo/Turku, FinlandBackground: Shedding of nanoparticles from the cell membrane is a common process in all cells. These nanoparticles are present in body fluids and can be harvested by isolation. To collect circulating nanoparticles from blood, a standard procedure consisting of repeated centrifugation and washing is applied to the blood samples. Nanoparticles can also be shed from blood cells during the isolation process, so it is unclear whether nanoparticles found in the isolated material are present in blood at sampling or if are they created from the blood cells during the isolation process. We addressed this question by determination of the morphology and identity of nanoparticles harvested from blood.Methods: The isolates were visualized by scanning electron microscopy, analyzed by flow cytometry, and nanoparticle shapes were determined theoretically.Results: The average size of nanoparticles was about 300 nm, and numerous residual blood cells were found in the isolates. The shapes of nanoparticles corresponded to the theoretical shapes obtained by minimization of the membrane free energy, indicating that these nanoparticles can be identified as vesicles. The concentration and size of nanoparticles in blood isolates was sensitive to the temperature during isolation. We demonstrated that at lower temperatures, the nanoparticle concentration was higher, while the nanoparticles were on average smaller.Conclusion: These results indicate that a large pool of nanoparticles is produced after blood sampling. The shapes of deformed blood cells found in the isolates indicate how fragmentation of blood cells may take place. The results show that the contents of isolates reflect the properties of blood cells and their interaction with the surrounding solution (rather than representing only nanoparticles present in blood at sampling) which differ in different diseases and may therefore present a relevant clinical parameter.Keywords: nanoparticles, nanovesicles, microparticles, microvesicles, cell–cell communication